Sustainable material awareness, belief and readiness in housing development / Kim Dung Thi Vu and Bao Ngoc Nguyen - Vu, Kim Dung Thi; Nguyen, Bao Ngoc (UiTM Press, 2021)
The construction industry is one of the industries accounting for a large proportion of Vietnam's overall GDP. It is also one of the least sustainable industries with extensive use of non-renewable resources. A study on the current situation of occupational awareness of sustainable building materials, identifying factors that prevent the diffusion of sustainable building materials is critical. The present study raised the theoretical basis of using sustainable building materials for the construction industry. Questionnaire data from 130 valid responses were used to carry out statistical analysis and make interpretation of results. The results indicate no significant difference between the two groups of respondents in awareness, belief, and readiness towards sustainable materials. The awareness and readiness levels are higher among construction practitioners who have experience. The present findings might suggest several courses of action to solve the problem of sustainable materials being overlooked. Our research suggests that it is essential for policymakers to encourage stakeholders to consider sustainability more seriously. The research findings have profound managerial implications that experienced practitioners might significantly impact the decision-making process in the realm of sustainable orientation. Future work should concentrate on integrating sustainable building materials into innovative and transformative practices in the construction industry.